2009
DOI: 10.1007/s11191-009-9190-x
|View full text |Cite
|
Sign up to set email alerts
|

A Conceptual Analysis of Evolutionary Theory for Teacher Education

Abstract: In this paper we present a schematic overview of the central concepts in evolutionary theory, setting them off against the background of widespread misconceptions about them. Our aim is to provide high school teachers with (1) an overview of those particular concepts that they can expect students to have difficulties with, (2) a comparison of students' alternative conceptions with the corresponding accepted scientific concepts and (3) some recommendations for teaching these concepts. We aim to improve the lear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(21 citation statements)
references
References 65 publications
0
14
0
6
Order By: Relevance
“…It was revealed that the problems of teaching evolution are generally philosophical, epistemological, and conceptual (Alters and Nelson 2002;Van Dijk and Reydon 2010;Smith 2010). More specifically, belief about nature of scientific knowledge and knowing (Rutledge and Mitchell 2002;Trani 2004), religious commitment (Aguillard 1999;Eve and Dunn 1990;Griffith and Brem 2004;Rutledge and Mitchell 2002;Trani 2004), worldviews (Cobern 1994), knowledge of evolution (Rutledge and Mitchell 2002;Trani 2004), belief regarding scientific validity of evolution (Aguillard 1999;BouJaoude et al 2010;Eve and Dunn 1990;Rutledge and Warden 2000;Trani 2004), the pressure from parents and administrators (Moore and Kraemer 2005), ineffective pedagogy in evolution education and traditional ways of teaching evolution (Alters and Nelson 2002;Nelson 2007;Ingram and Nelson 2005;Scharmann 1994), college coursework in biology in general, evolution in particular (Aguillard 1999), anxiety level (Scharmann and Harris 1992), and stresses and coping strategies to alleviate the stresses (Griffith and Brem 2004), were reported to influence teachers' curricular and instructional decision while teaching evolution.…”
Section: Introductionmentioning
confidence: 99%
“…It was revealed that the problems of teaching evolution are generally philosophical, epistemological, and conceptual (Alters and Nelson 2002;Van Dijk and Reydon 2010;Smith 2010). More specifically, belief about nature of scientific knowledge and knowing (Rutledge and Mitchell 2002;Trani 2004), religious commitment (Aguillard 1999;Eve and Dunn 1990;Griffith and Brem 2004;Rutledge and Mitchell 2002;Trani 2004), worldviews (Cobern 1994), knowledge of evolution (Rutledge and Mitchell 2002;Trani 2004), belief regarding scientific validity of evolution (Aguillard 1999;BouJaoude et al 2010;Eve and Dunn 1990;Rutledge and Warden 2000;Trani 2004), the pressure from parents and administrators (Moore and Kraemer 2005), ineffective pedagogy in evolution education and traditional ways of teaching evolution (Alters and Nelson 2002;Nelson 2007;Ingram and Nelson 2005;Scharmann 1994), college coursework in biology in general, evolution in particular (Aguillard 1999), anxiety level (Scharmann and Harris 1992), and stresses and coping strategies to alleviate the stresses (Griffith and Brem 2004), were reported to influence teachers' curricular and instructional decision while teaching evolution.…”
Section: Introductionmentioning
confidence: 99%
“…Asghar's (2013) study has revealed that majority of teachers have misconceptions about the basic theory and concepts of evolution. Again, many studies in the literature reveal myriad of misconceptions about the basic theory of evolution (Asghar, Wiles & Alters, 2007;BouJaoude et al, 2011;Deniz, Donelly, & Yılmaz, 2008;Fahrenwald, 1999;Graf & Soran, 2011;Kim & Nehm, 2010;Pazza, Penteado & Kavako, 2010;Smith, 2010;van Dijk & Reydon, 2010). In a study by , propective teachers were found to have the misconception that the exclusive scientific authority in evolution is Lamarck and Darwin.…”
Section: Necatibey Eğitim Fakültesi Elektronik Fen Ve Matematik Eğitimentioning
confidence: 99%
“…경쟁과 적응의 생물학적 정의는 논문 3편 (Kampourakis, 2013;Smith, 2010;van Dijk & Reydon, 2010), 생물학 사전(Iwanami Shoten, 1996) 1종, 브리태니커 백과사전, 일반생물학 (Freeman, 2011;Reece et al, 2011;Russell, 2008;Sadava et al, 2012;Starr et al, 2011), 진화학 (Futuyma, 2005;Strickberger, 2000), 생태학 (Kim et al, 2007;Smith & Smith, 2009;Townsend et al, 2002), 생리학 (Fox, 2001;Sherwood, 2004;Silverthorn, 2010 Table 3. Frameworks to analyze general meanings of competition and adaptation (Table 7).…”
Section: 경쟁과 적응의 생물학적 의미를 분석하기 위한 분석틀을 개발하기mentioning
confidence: 99%
“…그러므로 자원은 생존, 성장 그리고 생식을 위해 필수불가결하며 본질적으로 생명체 간 경쟁의 근원이 된다 (Townsend et al, 2002). 비역사적 정의에서 중요한 점은 선택적 역사가 아니라 현재의 이점이 다 (Kampourakis, 2013;van Dijk & Reydon, 2010 (Futuyma, 2005;Smith, 2010;van Dijk & Reydon, 2010 (Smith & Smith, 2009;Strickberger, 2000;van Dijk & Reydon, 2010 (Moore et al, 2002). 이렇듯 일상생활로부터 얻은 보편 지식이 과학적 지식과 혼합될 때 오개념이 형성되는 경우가 종 종 있으므로, 일상적 지식과 과학적 지식에 대한 차이를 비교하여 연구할 필요가 있다 (Cummins et al, 1994).…”
unclassified
See 1 more Smart Citation